“Luka Tak Terlihat”: Studi Kasus Tentang Labelling dan Pembentukan Konsep Diri Siswa dalam Bingkai Pendidikan Karakter Kristen di Sekolah - Helmi Yultrisani Rolantika Muris; Jonathan Leobisa (Pusat Riset dan Inovasi Nasional, 2026)
Schools are formal educational institutions that play a crucial role in transferring knowledge and shaping students' cognitive, psychomotor, and character development systematically and responsibly. While the